2006
DOI: 10.1038/ncpneph0151
|View full text |Cite
|
Sign up to set email alerts
|

Primary aldosteronism: diagnostic and treatment strategies

Abstract: Primary aldosteronism is caused by bilateral idiopathic hyperplasia in approximately two-thirds of cases and aldosterone-producing adenoma in one-third. Most patients with primary aldosteronism are normokalemic. In the clinical setting of normokalemic hypertension, patients who have resistant hypertension and hypertensive patients with a family history atypical for polygenic hypertension should be tested for primary aldosteronism. The ratio of plasma aldosterone concentration to plasma renin activity has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
224
0
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(236 citation statements)
references
References 87 publications
3
224
0
9
Order By: Relevance
“…At enrollment, 62 participants (12.1%) were current smokers, 182 (35.4%) reported intake of alcohol, 139 (27.0%) had hypercholesterolemia, 33 (6.4%) had diabetes mellitus and 19 (3.7%) had a history of cardiovascular disease. Two subjects (0.4%) had ARR X20 ng per 100 ml per ng ml -1 h -1 in the presence of PAC X15 ng per 100 ml, which was the cutoff value to screen for primary aldosteronism; 24,25 however, neither subject had hypertension or hypokalemia. The mean number of measurements for HBP was 23.2±6.0, and the mean systolic/diastolic HBP and CBP values of subjects were 117.2±13.6/73.2±8.8 and 128.9±13.1/ 72.1 ± 8.9 mm Hg, respectively.…”
Section: Participant Characteristicsmentioning
confidence: 94%
“…At enrollment, 62 participants (12.1%) were current smokers, 182 (35.4%) reported intake of alcohol, 139 (27.0%) had hypercholesterolemia, 33 (6.4%) had diabetes mellitus and 19 (3.7%) had a history of cardiovascular disease. Two subjects (0.4%) had ARR X20 ng per 100 ml per ng ml -1 h -1 in the presence of PAC X15 ng per 100 ml, which was the cutoff value to screen for primary aldosteronism; 24,25 however, neither subject had hypertension or hypokalemia. The mean number of measurements for HBP was 23.2±6.0, and the mean systolic/diastolic HBP and CBP values of subjects were 117.2±13.6/73.2±8.8 and 128.9±13.1/ 72.1 ± 8.9 mm Hg, respectively.…”
Section: Participant Characteristicsmentioning
confidence: 94%
“…Also, there is a lack of consensus on the types of patients' populations in which the ARR should be used as screening test for PA and on clear cut-off values to adopt. For example, Montori and Young, in a systematic review of 16 studies (for a total of 3,136 patients), reported that the thresholds for the ARR used varied between 7.2 and 100.0 ng/dL per ng/mL per hour [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Less common forms are the Unilateral Adrenal Hyperplasia (UAH), that is the micro-or macronodular hyerplasia of the zona glomerulosa of the adrenal cortex, mainly involving one of the adrenal glands (3%); and the bilateral adrenal hyperplasia, micro-or macronodular (1%) [3,4] Even if sporadic, PA may be familial and manifests in at least two forms [5,6]: the Familial Hyperaldosteronism type I (FH-I), or Glucocorticoid-Remediable Aldosteronism (GRA), very rare (< 1%), which has an autosomal dominant mode of transmission and is caused by an adrenocorticotropic hormone-regulated, hybrid CYP11B1/ CYP11B2 gene [7,8]; and the familial hyperaldosteronism type II (FH-II), which is the familial form of APA or BAH or both. FH-II relative frequency is unknown, but it is considered to be at least 5 times higher than that of FH-I.…”
Section: Introductionmentioning
confidence: 99%
“…5 Bentuk yang umum dari hiperaldosteronisme primer adalah idiopathic bilateral hyperplasia (IHA) dan aldosterone-producing adenoma (APA). 6 Hiperplasia adrenal unilateral jarang ditemui, namun diagnosis ini dapat dipertimbangkan bila tes lateralisasi, seperti adrenal venous sampling (AVS) positif, tetapi pemeriksaan histologi dan radiologi tidak mendeteksi adanya suatu adenoma. Sekitar 1% pasien hiperaldosteronisme primer merupakan kasus karsinoma adrenal yang memproduksi aldosteron.…”
Section: Diskusiunclassified